Sistem Pendukung Keputusan Aplikasi Bantu Pembelajaran Matematika Menggunakan Metode EDAS - Karim, Abdul; Esabella, Shinta; Hidayatullah, Muhammad; Andriani, Titi (Forum Kerjasama Pendidikan Tinggi, 2022)
Technological developments have occurred at this time. The rapid development of technology forces students to be wiser in using it. One of the functions of technology is to become a learning medium like a cell phone. HP, which has become an obligation for students, has given rise to ideas for experts to bring up many new applications, especially in the field of mathematics. The emergence of these various applications makes students confused to choose which one is feasible to choose. To solve this problem, a Decision Support System is needed. SPK is a computer-based system whose function is to assist parties or individuals who need it, especially in making a decision. SPK can function properly, if you use the method. The method used in Ono's research is the EDAS method. The EDAS method is a method that uses a formula or formula, where the decision is generated from positive and negative distances. Based on this study, the results were found, namely alternative A1 with the name of the application, namely QANDA with a value of 0.0767 as the highest score